2012
DOI: 10.1371/journal.pone.0048287
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of the Soybean to Enhance the β-Carotene Content through Seed-Specific Expression

Abstract: The carotenoid biosynthetic pathway was genetically manipulated using the recombinant PAC (Phytoene synthase-2A-Carotene desaturase) gene in Korean soybean (Glycine max L. cv. Kwangan). The PAC gene was linked to either the β-conglycinin (β) or CaMV-35S (35S) promoter to generate β-PAC and 35S-PAC constructs, respectively. A total of 37 transgenic lines (19 for β-PAC and 18 for 35S-PAC) were obtained through Agrobacterium-mediated transformation using the modified half-seed method. The multi-copy insertion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 34 publications
3
61
1
2
Order By: Relevance
“…Overexpression of the genes related to the carotenoid biosynthesis pathway in rapeseed (Shewmaker et al, 1999), rice endosperm (Ye et al, 2000), potato tuber (Ducreux et al, 2005), and soybean (Kim et al, 2012) can significantly increase the content of carotenoids in these crops. PSY is the first rate-limiting enzyme in the synthesis process of carotenoid production and the regulation metabolic of geranylgeranyl pyrophosphate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the genes related to the carotenoid biosynthesis pathway in rapeseed (Shewmaker et al, 1999), rice endosperm (Ye et al, 2000), potato tuber (Ducreux et al, 2005), and soybean (Kim et al, 2012) can significantly increase the content of carotenoids in these crops. PSY is the first rate-limiting enzyme in the synthesis process of carotenoid production and the regulation metabolic of geranylgeranyl pyrophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…PSY is the first rate-limiting enzyme in the synthesis process of carotenoid production and the regulation metabolic of geranylgeranyl pyrophosphate. Previous studies demonstrated that the constitutive and specific expression of PSY could significantly improve the content of carotenoid in the tissues of higher plants, which has also become the basis of genetically modified carotenoid genes in plants (Shewmaker et al, 1999;Ye et al, 2000;Fraser et al, 2002;Ducreux et al, 2005;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids were extracted and measured using HPLC as described previously (Kim et al, 2012a). Briefly, the carotenoids were extracted from rice samples (0.12 g) by adding 3 mL of ethanol containing 0.1% (w/v) ascorbic acid, vortex mixing for 20 s, and placing in a water bath at 85°C for 5 min.…”
Section: Measurement Of Carotenoid Contentsmentioning
confidence: 99%
“…Golden rice is a glaring example of this promotion (Ye et al, 2000;Paine et al, 2005). Other metabolically manipulated plants for carotenoid improvement are tomato (Fray et al, 1995) canola (Shewmaker et al, 1999), wheat (Cong et al, 2009), potato (Romer and Fraser, 2005), and soybean (Kim et al, 2012). However, knowledge about the role of genes involved in carotenoids biosynthesis for induction of salt tolerance and their expression analyses remained obscure.…”
Section: Discussionmentioning
confidence: 99%